Siyasah sebagai Prinsip Politik Islam dalam Menjaga Hak Minoritas dan Mengelola Keragaman Pluralitas - Ahmad Fakhri Wardana; Meutya Ramdhani Zalsabila; Kurniati (4, 2025)
This study examines the role of siyasa as a political principle in Islam that is oriented towards efforts to maintain and fulfill the rights of non-Muslim citizens in Indonesia, which is pluralistic in terms of religion, ethnicity, and culture. As a country with the largest Muslim population in the world, Indonesia has a strong constitutional foundation in guaranteeing religious freedom and the protection of human rights for all citizens without discrimination. However, in social and political practices, various challenges are still encountered in the form of intolerance, marginalization, and discriminatory treatment of religious minorities that often contradict the values ​​of Pancasila and the mandate of the 1945 Constitution. Through a qualitative approach with historical methods and literature analysis, this study examines the concept of fiqh siyasah and its relevance in the context of the modern Indonesian state that adheres to a democratic system and the principle of the rule of law. Fiqh siyasah is understood not merely as a theory of power, but as an ethical framework that emphasizes the values ​​of justice (al-‘adl), deliberation (shura), equal rights, and the public good (maslahah ‘ammah). These principles align with the primary objectives of Islamic law (maqasid al-shariah), particularly in safeguarding religion, life, intellect, property, and human dignity. The results of this study indicate that the application of siyasa values ​​in public policy can strengthen the protection of minority rights if accompanied by consistent law enforcement, inclusive policy reform, and education for pluralism and tolerance in various aspects of life. Thus, siyasa functions not only as an Islamic moral guideline but also as a strategic instrument for realizing a just, harmonious, and inclusive Indonesian society for all citizens, regardless of religious or belief differences. Abstrak Penelitian ini mengkaji peran siyasah sebagai prinsip politik dalam Islam yang berorientasi pada upaya menjaga dan memenuhi hak-hak warga negara non Muslim di Indonesia yang plural secara agama, etnis, dan budaya. Sebagai negara dengan populasi Muslim terbesar di dunia, Indonesia memiliki landasan konstitusional yang kuat dalam menjamin kebebasan beragama serta perlindungan hak asasi manusia bagi seluruh warga negara tanpa diskriminasi. Namun demikian, dalam praktik sosial dan politik, masih dijumpai berbagai tantangan berupa sikap intoleransi, marginalisasi, dan perlakuan diskriminatif terhadap kelompok minoritas agama yang sering kali bertentangan dengan nilai Pancasila dan amanat Undang-Undang Dasar 1945. Melalui pendekatan kualitatif dengan metode historis dan analisis literatur, penelitian ini menelaah konsep fiqh siyasah serta relevansinya dalam konteks negara modern Indonesia yang menganut sistem demokrasi dan prinsip negara hukum. Fiqh siyasah dipahami tidak sekadar sebagai teori kekuasaan, tetapi sebagai kerangka etis yang menekankan nilai keadilan (al-‘adl), musyawarah (shura), persamaan hak, dan kemaslahatan umum (maslahah ‘ammah). Prinsip-prinsip tersebut sejalan dengan tujuan utama syariat Islam (maqasid al-shariah), khususnya dalam menjaga agama, jiwa, akal, harta, dan kehormatan manusia. Hasil dari Penelitian ini menunjukkan bahwa penerapan nilai-nilai siyasah dalam kebijakan publik dapat memperkuat perlindungan hak-hak minoritas jika diiringi dengan penegakan hukum yang konsisten, reformasi kebijakan yang inklusif, serta pendidikan pluralisme dan toleransi di berbagai lini kehidupan. Dengan demikian, siyasah berfungsi tidak hanya sebagai pedoman moral keislaman, tetapi juga sebagai instrumen strategis untuk mewujudkan tatanan masyarakat Indonesia yang adil, harmonis, dan inklusif bagi seluruh warga negara, tanpa memandang perbedaan agama atau keyakinan.